OP21 Prevalence of advance care planning documentation and self-reported uptake in oncology patients: findings from a national australian survey. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Blaschke, SM; Sellars, M; Detering, K; Kelly, H; Nolte, L
Abstract : Background: Absence of data on Advanced Care Directive (ACD) completion makes evaluation of Advance Care Planning (ACP) implementation challenging. This study reports the prevalence, accessibility and characteristics of ACDs for people with cancer aged 3 65 years from Australian hospital, primary care and aged care facilities. Methods: Prospective cross-jurisdictional study consisting of health record audit and self-report survey. Result: 51 sites and 2285 participants were included; 458 of whom had cancer. Of these, 27% had an ACD located in their record; 3% statutory stated preferences for care, 10% appointed substitute decision-maker, and 19% were non-statutory document. Most (83%) treatment plans were consistent with ACD preferences. More participants with cancer were receiving palliative care (11%) compared to the overall sample (4%). 97 participants with cancer completed the survey, 58% reported they had completed ACP documentation; 30% indicated trusting their children to make medical decisions; 26% trusted their partners, and 19% their doctors. Conclusion(s): This study is the first to examine ACP documentation prevalence in an Australian cancer population, at the point of care, and across jurisdictions. Whilst 27% of participants had an ACD located during the audit, more people self-reported having completed ACP documentation, which is encouraging as documentation available at point of care is likely to influence care. Only a low percentage of people were recorded as receiving palliative care. Recommendations to improve ACP uptake include: workforce education, care pathway inclusive of ACP and accessibility should be supported by national systems such as "My Health Record".